Nepali translation, cross-cultural adaptation and measurement properties of the Shoulder Pain and Disability Index (SPADI) - Sudarshan KC; Saurab Sharma; Karen Ginn; Tawfiq Almadi; Darren Reed (Journal of Orthopaedic Surgery and Research, 2019)
Abstract Background The Shoulder Pain and Disability Index (SPADI) is a 13-item shoulder-specific patient-reported outcome measure (PROM). The English version is easy to use and has demonstrated excellent measurement properties for both clinical and research settings. The availability of the SPADI in Nepali would facilitate shoulder research and enhance management of patients with shoulder pain in Nepal. Therefore, the purpose of this study was to translate and cross-culturally adapt the SPADI into Nepali (SPADI-NP) and evaluate its measurement properties. Methods The translation and adaptation process followed international guidelines. Participants completed SPADI-NP on two assessments (N = 150 at initial and 119 at follow-up assessment). A Nepali version of the Global Rating of Change score was completed at follow-up. Assessment of measurement properties included analysis of internal consistency (Cronbach’s α), minimal detectable change (MDC) with standard error of measurement (SEM), test-retest reliability (intraclass correlation coefficient; ICC), validity (factor structure, construct using Pearson’s correlation with the Disability of Arm and Hand [DASH]) and responsiveness (area under the curve; AUC) with minimal important change (MIC). Results Minor changes were integrated in the adaptation process to improve cultural relevance such as dress items. Items were largely loaded under two factors (pain and disability), internal consistencies were good for the pain construct (α = 0.82) and disability (α = 0.88) and test-retest reliability was excellent (pain = 0.89, disability = 0.96). MDC was 5.7 (out of 100) with SEM = 2.1. Strong associations with the DASH (r = 0.63 pain, r = 0.81 disability) demonstrated its construct validity. The AUC was 0.68 and MIC was 12.3 (out of 100). Conclusion The Nepali version of the SPADI demonstrated excellent reliability and validity. It can be used for the assessment of shoulder pain and disability in patients with shoulder pain in Nepal in both clinical practice and research.